Concussion‐Related Health Care Utilization Among Medicaid Insured Children in Ohio: Rural and Urban Differences. Issue 3 (3rd August 2020) - Sullivan, Lindsay; Newton, Alison; Shi, Junxin; Chang, Teng‐Jen; Yang, Jingzhen
Abstract: Purpose: The current study examines rural‐urban differences in trends in rates and type of concussion‐related health care utilization over time from 2008 to 2016 among Medicaid insured children in Ohio. Methods: We analyzed Medicaid claims for health care utilization for diagnosed concussions among children aged ≤18 years between April 1, 2008, and December 31, 2016. We compared the trends in rates of concussion‐related health care utilization between children who lived in rural and urban areas using Poisson regressions. We examined trends in the type of concussion‐related health care utilization by location of residence using linear regressions. Findings: We found a significant increase in health care utilization for concussion over time, with rates of treated concussion consistently higher in rural children compared to urban children ( P < .0001) throughout the study period. Although initial care at the Emergency Department (ED) remained the most common type of initial concussion‐related health care utilization for rural children throughout the study period, the most common type of initial care sought by urban children shifted over time from the ED to primary care providers (PCPs). For both rural and urban children, PCPs remained the most common type of follow‐up care sought throughout the study period, with no significant rural‐urban differences in the trends of follow‐up care sought through PCPs over time. Conclusions: We observed significant rural‐urban differences in the trends in rates and types of concussion‐related health care utilization over time from 2008 to 2016. Future studies are needed to further our understanding of the effect of these observed rural‐urban differences on concussion recovery.